Reclaiming heritage: colourization, culture wars and the politics of nostalgia - Grainge, Paul (Routledge, 1999)
This article considers the discursive continuities between a specifically liberal defence of cultural patrimony, evident in the debate over film colourization, and the culture war critique associated with neo-conservatism. It examines how a rhetoric of nostalgia, linked to particular ideas of authenticity,canonicity and tradition,has been mobilized by the right and the left in attempts to stabilize the confguration and perceived transmission of American cultural identity. While different in scale, colourization and multiculturalism were seen to create respective (postmodern) barbarisms against which defenders of culture, heritage and good taste could unite. I argue that in its defence of the ‘classic’ work of art, together with principles of aesthetic distinction and the value of cultural inheritance,the anti-colourization lobby helped enrich and legitimize a discourse of tradition that, at the end of the 1980s, was beginning to reverberate powerfully in the conservative challenge to a ‘crisis’ within higher education and the humanities. This article attempts to complicate the contemporary politics of nostalgia, showing how a defence of cultural patrimony has distinguished major and minor culture wars, engaging left and right quite differently but with similar presuppositions.